Obligate endosymbiosis enables genome expansion during eukaryogenesis - Samuel H. A. von der Dunk; Paulien Hogeweg; Berend Snel (Communications Biology, 2023)
Abstract The endosymbiosis of an alpha-proteobacterium that gave rise to mitochondria was one of the key events in eukaryogenesis. One striking outcome of eukaryogenesis was a much more complex cell with a large genome. Despite the existence of many alternative hypotheses for this and other patterns potentially related to endosymbiosis, a constructive evolutionary model in which these hypotheses can be studied is still lacking. Here, we present a theoretical approach in which we focus on the consequences rather than the causes of mitochondrial endosymbiosis. Using a constructive evolutionary model of cell-cycle regulation, we find that genome expansion and genome size asymmetry arise from emergent host–symbiont cell-cycle coordination. We also find that holobionts with large host and small symbiont genomes perform best on long timescales and mimic the outcome of eukaryogenesis. By designing and studying a constructive evolutionary model of obligate endosymbiosis, we uncovered some of the forces that may drive the patterns observed in nature. Our results provide a theoretical foundation for patterns related to mitochondrial endosymbiosis, such as genome size asymmetry, and reveal evolutionary outcomes that have not been considered so far, such as cell-cycle coordination without direct communication.